1989
DOI: 10.1016/0168-6445(89)90004-1
|View full text |Cite
|
Sign up to set email alerts
|

Glucose transport in Escherichia coli

Abstract: 13J.3. The glucose perm eases of E. coli E. coli and S. typhimurium both have two glucose-specific permeases. One, the glucose permease proper, is specific for glucose and the non-0168-6445/89/$03.50

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 63 publications
1
23
0
Order By: Relevance
“…Kofoid and Parkinson (11, lla) showed that a stretch of 209 residues at the C terminus of EIIGic exhibits a sequence similarity of 39% with the transmitter consensus motif of sensor proteins that they defined. Consistent with the properties expected for a transmitter module, the C-terminal end of EIIGIc comprising about 90 residues has hydrophilic properties, and biochemical experiments suggest that this region might be exposed at the cytoplasmic face of the membrane (8). These observations argue in favor of the notion that the membranebound EIIGIc might be a sensor protein resembling those of the two-component systems.…”
Section: Discussionsupporting
confidence: 65%
“…Kofoid and Parkinson (11, lla) showed that a stretch of 209 residues at the C terminus of EIIGic exhibits a sequence similarity of 39% with the transmitter consensus motif of sensor proteins that they defined. Consistent with the properties expected for a transmitter module, the C-terminal end of EIIGIc comprising about 90 residues has hydrophilic properties, and biochemical experiments suggest that this region might be exposed at the cytoplasmic face of the membrane (8). These observations argue in favor of the notion that the membranebound EIIGIc might be a sensor protein resembling those of the two-component systems.…”
Section: Discussionsupporting
confidence: 65%
“…Two-dimensional NMR studies have established the validity of this conclusion, showing that this N-terminal region of the HAgkC domain is highly mobile, exhibiting essentially unrestricted intramolecular motion (Stone et al, 1992). Interdomain Q-linkers and alanine/ proline-rich hinges that occur in the boundaries of functionally and structurally distinct but otherwise interacting domains of other PTS permeases have also been identified (Erni, 1989;Sutrina et al, 1990;Wu et al, 1990). The sequences depicted in Figure 4 reveal that all protein members of the Enzyme I family contain putative Q-linkers at the ends of regions I11 shown in Figure 3.…”
Section: Putative Flexible Linkers In Enzyme I Family Proteinsmentioning
confidence: 88%
“…The bacterial uptake of unlabeled glucose in E. coli occurs by active transport across the IM. Here, glucose molecules are bound to the periplasmic permease(s), then translocated and phosphorylated at the C6 atom, and released into the cytoplasm (50). The uptake of NBDG was proven to be specifically mediated by the phosphoenolpyruvate phosphotransferase system (51).…”
Section: Fluorescent Substratesmentioning
confidence: 99%